Crime at Work Vol 1
VII, 228 p.
Keywords: This book contains a wealth of information providing essential reading for all those interested in crime prevention, the motivation of different types of offenders and the effectiveness of various security measures. There has been little consideration of the extent, impact and patterns of crimes in the workplace. This important text suggests that such an omission is no longer justified and reflects the growing realization that effective responses to crime are based on the need to collect and share information.